Development of 3-axis motion simulator and precision PMSM drives - Xie, Yue. (2008)
In this thesis, the development of a 3-axis motion simulator as well as its motion controller, which are used to simulate satellite attitude behavior and then provide laboratory environment for development and testing of satellite instruments, is introduced. This thesis covers the following five research topics on the motion simulator development and related aspects such as permanent magnet synchronous motor (PMSM) drives and Hardware-inthe-loop simulation (HILS) dynamics: (1) Design, development and modeling of a three-axis motion simulator; (2) Development of integral control strategies for the motion simulator; (3) PMSM motion control with initial rotor position uncertainty; (4) IPMSM wide-speed operation; and (5) Preliminary HILS dynamics analysis.